Knowledge and attitudes toward over-the-counter medications among pharmacy students: insights from a cross-sectional study in Taif University, Saudi Arabia - Alharthi, Mohammed S.; Almalki, Hassan; Alsubaie, Faisal; Alotaibe, Fawaz; Abuasiah, Abdullah; Basha, Faisal; Aldurdunji, Mohammed M.; Alorfi, Nasser M. (Frontiers in Medicine, 2024)
Introduction Over-the-counter (OTC) medications are those obtained without a medical prescription from a healthcare professional. With the increasing availability of information from various sources, including social media, pharmacy students may be exposed to unreliable or inaccurate data. Incorrect medication use is particularly concerning due to its potential risk of causing adverse health effects.” Hence, this study aims to determine students’ knowledge and attitudes at Taif University’s pharmacy college. Methods This research utilized a cross-sectional online questionnaire-based study, employing data from a sample of 450 pharmacy students from Taif University in Saudi Arabia. Descriptive analysis included descriptive and differential analysis. The data were analyzed using statistical package for social sciences (SPSS) Version 27. Results The majority of participants, 297 (88.2%), were aware that inappropriate use of over-the-counter medications might have negative implications. A total of 233 participants (51.8%) reported having previously used an OTC medication. Also, 293 (65.1%), were aware that using OTC medications beyond their expiration date was harmful. A total of 280 participants (62.2%) had a high knowledge of OTC medication, whereas 170 respondents (37.8%) had a low level of knowledge. A significant correlation was found between age, year of study, and the use of OTC medication p-values <0.05 (0.016*, 0.003*, and 0.001* respectively) and understanding of OTC medication. Gender had no significant influence on knowledge of OTC (p > 0.05). Conclusion The study found positive attitudes toward OTC medications. Due to increased pharmaceutical exposure and self-medication, upper-year students and OTC course graduates comprehend OTC medications better. The examination found safety protocol violations in expiration dates, prescription label interpretation, and storage. Therefore, the study provides useful information for future attempts. Also, this study may contribute to the literature and guide future research to fill knowledge gaps.